A review of thermo physical properties of nanofluids. (2019) - Kumar Gupta, Naveen; Mishra, Shashwat; Kumar Tiwari, Arun; Kumar Ghosh, Subrata
Abstract: Nanofluids are the new class of thermo fluidics and also an emerging area for research. Due to their superior thermo physical properties, researchers were attracted towards their application in different thermal devices. Researchers claimed that the positive impact of the thenanofluid application on thermal performance is due to their enhanced thermal properties like thermal conductivity, specific heat, and viscosity etc. The goal of this review is to provide an overview of thermo physical properties of nanofluids. All parameters have individual or combined effects on thermo physical properties of nanofluids. Authors have drawn the attention of the research community to explore the dependency of all parameters on each other.